Tensile characteristics of polymethyl methacrylate polymer concrete under different strain rates - Sagar Acharya; Mohamed A. Moustafa; Shahrukh Shoaib (Case Studies in Construction Materials)
Material strength characterization tests are essential for evaluating a material's suitability for structural applications. Tensile strength, a crucial property of concrete, indirectly contributes to the shear capacity of structural components. While conventional concrete typically has lower tensile strength, polymer concrete, such as polymethyl methacrylate polymer concrete (PMMA-PC), can exhibit significantly higher tensile strength. The adaptability of polymer concrete in the construction industry underscores the need for experimental evidence on its mechanical properties. This study presents new data on the uniaxial tensile properties of PMMA-PC. PMMA-PC specimens were tested with seven different strain rates ranging from 10−4/s to 100/s under monotonic loading for dogbone and prismatic specimens with and without aggregates. The results revealed that the tensile strength of PMMA-PC was significantly higher than that of conventional concrete, a noteworthy finding. Moreover, prismatic specimens with and without aggregates exhibited higher tensile strength than those of dogbone specimens. The tensile strength of PMMA-PC was found to depend on the applied strain rate, leading to the development of new empirical correlations between tensile strength and strain rate for PMMA-PC.